Geographical distribution of hard ticks (Acari:Ixodidae) and tick-host associations in Benin, Burkina-Faso, Ivory-Coast and Togo - YESSINOU, R. ERIC; Cazan, Cristina Daniela; Bonnet, Sarah Irène; FAROUGOU, SOUAÏBOU; Mihalca, Andrei Daniel (My University, 2022)
Knowledge of ticks and associated pathogens is crucial to assess the risk of exposure of humans and animals to pathogens. For this review, we collected relevant data from published articles and field collections to provide an update on the biodiversity of ticks, and tick-host associations in four countries of West Africa: Benin, Burkina- Faso, Ivory-Coast, and Togo. The literature review was done according to Preferred Reporting Items for Sys- tematic Reviews and Meta-Analysis (PRISMA) guidelines. The search was limited to literature published from 1953 to 2021 in English and French sources. Out of 104 articles retrieved, only 41 studies met the eligibility criteria and were included in the review. The final database included a total of 53,619 adults, nymphs and larval ticks belonging to 24 species and five genera (Amblyomma, Haemaphysalis, Hyalomma, Ixodes and Rhipicephalus) that were collected from 23 different species of wild and domestic animals. This is the first record of Ixodes aulacodi and Rhipicephalus simpsoni in Benin, together with two new host records for A. latum. This checklist allows an update on tick-host associations and provides information on the diversity of ticks in West Africa.
Keywords: Host-parasite interaction; biodiversity of ticks; animal; tick-borne pathogens; West Africa